PARTISIPASI MASYARAKAT DALAM PELAKSANAAN WISATA DI DESA WISATA RANTIH SAWAHLUNTO - Annisa "; Musadad " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Rantih village is the only tourist village in Sawahlunto. Rantih touristvillage is managed and developed by the local community. Therefore, this studyaims to know the form of participation, communities in developing Rantih touristvillage and the encouraging&inhibiting factors of the in participating. This studyuser descriptive qualitative method. The key informant is business ownerscommunity, supporting informant is the headman, heads of organization and othercommunities. Data collection was taken by direct observation, interviews anddocumentation. Data analysis was done with data reduction, data display andconclusion. The result of this study concluded that: 1) The implementation ofbusiness activities by community has runs well althought not completely optimal.2) Implementation of the form of community participation directly, indirect andnon participant. 3) The obstacles include people’s mindset and tourist villageorganization.Key word : Community Participation, Implementation, Tourist village Rantih